The boy who saw Bigfoot - Place, Marian T. (Marian Templeton), 1910-2006. (New York : Dodd, Mead, 1979)
A ten-year-old boy, placed once again with new foster parents, becomes involved in a search for Bigfoot.
Keywords: Sasquatch -- Fiction; Foster home care -- Fiction; Forests and forestry -- Fiction; Washington (State) -- Fiction